May the trophy evaluation variables be utilized as population indices in cervids : example of the red deer from the hilly part of the Pannonian plain? = Mogu li elementi ocjene trofeja poslužiti kao populacijski indeksi u cervida? : Primjer na jelenu običnom iz brdskog područja Panonske nizine - Jumić, Vlado (Array, 2021)
The most frequently utilized population quality indices in cervids were a fluctuating asymmetry or a branch length in yearlings. Nevertheless, unlike bovids, there has not been a reliable quality index so far that could also be applied at a later age. Therefore, an application reliability testing pertaining to certain elements of trophy measurement for the sake of difference detection between the cohorts was performed on a sample numbering 225 trophies of red deer stags from 11 cohorts. Although each of the nine trophy variables tested has succeeded in finding certain differences, the most reliable are the overall trophy value and circumferences (circumference of coronets, lower beam circumference and upper beam circumference). Since various trophy evaluation systems have been applied in the world, the implementation of the overall trophy value is limited only to the trophies evaluated pursuant to the CIC system. Hence, the most reliable indices are those based upon circumferences.